Experiencias significativas con estudiantes de educación universitaria para la producción de textos académicos: Significant Experiences with University Education Students for the Production of Academic Texts - Almidón Ortiz, Carlos Alcides; Almidón, Ángel; Landeo Quispe , Alex Sandro (Universidad del Zulia, 2021)
The purpose of the study was to present the experiences obtained with the students of the National University of Huancavelica, about the production of academic texts in the classroom. All this originated from the teachers' need to develop their writing competence, with regard to the production of texts in the classroom, having their theoretical-methodological antecedents in authors such as Moreno (1998), Beaugrande and Dressler (1997) Villasmil and Fuenmayor (2014), Fuenmayor and Villasmil (2016). The research was qualitative in nature. The sample was made up of students from the Professional School of Systems Engineering and Electronics. This research was divided into several stages, among which are the bibliographic review carried out by the researchers on aspects related to written production, the relationship between sociolinguistic theory with the didactics of the language and the rules of textuality. After this review, the researchers applied an intervention plan to the students that contemplated the aspects inherent to the writing process and finally they were asked to produce a text in the classroom related to some social event, three of the texts were randomly selected. The analysis determined that, in their production, the students showed influence of social facts, textuality norms, the world of life, its situational context, describing a common reality between the writer and the reader, as well as affective traits and an intention communicative, novel and interesting information, wanting to communicate something.